HEAT TREATMENT METHOD FOR ELECTROPLATED Fe-Ni ALLOY FILM AND ELECTROPLATED Fe-Ni ALLOY FILM
By annealing and gas quenching and cooling the electroformed Fe-Ni alloy foil under pressure, the problem of shape deformation and high thermal expansion coefficient during the heat treatment process of Fe-Ni alloy foil is solved, and low thermal expansion is achieved Coefficient and excellent mechanical properties.
Patent Information
- Application Number
- CN202380050622.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-01-25
- Filing Date
- 2023-06-26
- Publication Date
- 2025-02-18
AI Technical Summary
The existing Fe-Ni alloy foil is prone to deformation of shape, such as curling or wrinkling during the heat treatment process, and has a high thermal expansion coefficient, making it difficult to meet the needs of high-resolution equipment such as OLED displays.
Thermomechanical heat treatment method is adopted to anneale the electroformed Fe-Ni alloy foil under pressure, the annealing temperature is between 180 and 600°C, the applied pressure is at least 0.1 KPa, and gas quenching and cooling is performed after annealing.
It effectively suppresses shape deformation during heat treatment, reduces the thermal expansion coefficient, and improves mechanical properties, making Fe-Ni alloy foil suitable for precision applications such as high-resolution OLED displays.
Smart Images

Figure CN119487223A_ABST
Abstract
Description
Background of the Invention Technical Field
[0002] This invention relates to a method for heat-treating Fe-Ni alloy foil prepared by electroforming, and more specifically, to a heat treatment method that can reduce shape deformation such as curling or wrinkling during heat treatment and obtain a low coefficient of thermal expansion by thermomechanical heat treatment of Fe-Ni alloy foil, and Fe-Ni alloy foil prepared by this method.
[0003] The fine metal mask (FMM) used in OLED display deposition processes is manufactured through a series of processes, including melting, casting, rolling, and etching of Invar alloy, which has a very low coefficient of thermal expansion.
[0004] To increase the resolution of current OLED displays in smartphones from QHD (600ppi) to next-generation UHD levels (above 1000ppi), the wall thickness of the FMM apertures needs to be reduced to below 10μm to prevent obstruction of OLED material deposition.
[0005] However, rolling processes cannot produce Invar foils with a thickness of less than 25 μm. To address the need for higher resolution OLEDs, current methods involve rolling and etching foils to a thickness of approximately 13 μm. However, the top-down approach of melting, casting, rolling, and etching produces almost no ultrathin foils with a thickness of less than 10 μm, due to inclusions and increased production costs, and also results in significantly increased manufacturing costs.
[0006] Therefore, electroforming, a bottom-up method, has been studied for the manufacture of Fe-Ni alloy foils and fine metal masks.
[0007] Electroformed Fe-Ni alloy foil and FMM do not have the low coefficient of thermal expansion required for FMM, which is below 3 ppm / ℃ (preferably below 2 ppm / ℃), and therefore heat treatment is essential for reducing the coefficient of thermal expansion and enhancing mechanical properties.
[0008] However, heat treatment processes cause significant shape deformation, such as curling or wrinkling in Fe-Ni alloy foils and pattern deformation in FMMs, thus hindering the current use of these materials in FMM manufacturing. Summary of the Invention
[0009] One aspect of the present invention provides a method for heat-treating Fe-Ni alloy foil that suppresses deformation caused during the heat treatment process of Fe-Ni alloy foil prepared by electroforming and provides a low coefficient of thermal expansion and satisfactory mechanical properties.
[0010] Another aspect of the present invention provides an electroformed Fe-Ni alloy foil that exhibits a low coefficient of thermal expansion and excellent mechanical properties.
[0011] According to an embodiment of the present invention, a method for heat-treating Fe-Ni alloy foil is provided, which includes annealing an electroformed Fe-Ni alloy foil under pressure.
[0012] In the heat treatment of Fe-Ni alloy foil, annealing can be carried out at temperatures ranging from 180 to 600°C.
[0013] In the heat treatment of Fe-Ni alloy foil, annealing can be carried out for a duration of 1 minute to 12 hours.
[0014] In the method of heat-treating Fe-Ni alloy foil, the pressure applied to the Fe-Ni alloy foil can be at least 0.1 kPa.
[0015] In the heat treatment method of Fe-Ni alloy foil, the Fe-Ni alloy foil can be subjected to pressure and tensile force in one direction.
[0016] In the heat treatment method of Fe-Ni alloy foil, the Fe-Ni alloy foil can be subjected to pressure and tensile forces in two directions perpendicular to each other.
[0017] In the heat treatment method of Fe-Ni alloy foil, gas quenching can be performed in an inert gas atmosphere after annealing.
[0018] In methods for heat-treating Fe-Ni alloy foil, gas quenching may include cooling in an inert gas environment.
[0019] In the heat treatment of Fe-Ni alloy foil, gas quenching can be performed in a sealed chamber filled with inert gas.
[0020] In the heat treatment method of Fe-Ni alloy foil, the annealing of Fe-Ni Invar alloy foil can be carried out by a continuous heat treatment process, wherein the foil is continuously fed through a heating furnace.
[0021] In the method of heat treating Fe-Ni alloy foil, a tensile force can be applied in the direction of travel of the Fe-Ni Invar alloy foil during a continuous heat treatment process.
[0022] In a method for heat-treating Fe-Ni alloy foil, pressure can be applied while the travel of the Fe-Ni alloy foil is temporarily stopped during a continuous heat treatment process.
[0023] In the method of heat treating Fe-Ni alloy foil, during the continuous heat treatment process, a tensile force can be applied in a direction perpendicular to the travel direction of the Fe-Ni Invar alloy foil.
[0024] In the method of heat treating Fe-Ni alloy foil, tensile force can be applied in the direction of travel of the Fe-Ni Invar alloy foil and in a direction perpendicular to it during the continuous heat treatment process.
[0025] In the heat treatment of Fe-Ni alloy foil, the continuous heat treatment process can be combined with the electroforming process of Fe-Ni Invar alloy foil in a roll-to-roll manner.
[0026] According to another embodiment of the present invention, an Fe-Ni alloy foil prepared by electroforming is provided, wherein more than 90% of the total volume of the Fe-Ni alloy foil has a face-centered cubic (FCC) structure and a (111) peak of the highest strength as determined by XRD analysis.
[0027] In Fe-Ni alloy foil, the Fe-Ni alloy foil may have an average grain size of less than 100 nm, preferably less than 80 nm, and more preferably less than 50 nm.
[0028] In Fe-Ni alloy foil, the tensile strength can be from 0.7 to 1.5 GPa.
[0029] In Fe-Ni alloy foil, the Fe-Ni alloy may contain 33 to 43% by mass of Ni.
[0030] In the Fe-Ni alloy foil, the Fe-Ni alloy foil may have a thickness of less than 15 μm, less than 14 μm, less than 13 μm, less than 12 μm, less than 11 μm, less than 10 μm, less than 9 μm, less than 8 μm, less than 7 μm, less than 6 μm, or less than 5 μm, and the thicknesses are presented as examples, and the present invention does not intend to exclude thicknesses greater than 15 μm.
[0031] In Fe-Ni alloy foil, Fe-Ni alloy foil can be used for fine metal masks or OLED encapsulation materials, but the uses are presented as examples and are not intended to be exhaustive or limiting. Attached Figure Description
[0032] Figure 1 This is a schematic diagram showing a thermomechanical heat treatment method according to an embodiment of the present invention;
[0033] Figure 2 The shapes of the sample (gas quenched) from Example 1 and the sample (uncooled) from Example 2 are shown;
[0034] Figure 3 The results show the coefficients of thermal expansion of the sample from Example 1 (gas quenched) and the sample from Example 2 (uncooled) measured in the range of 50°C to 100°C.
[0035] Figure 4 The shapes of the samples from Example 3 before and after heat treatment are shown;
[0036] Figure 5 The shapes of the sample from Example 4 before and after heat treatment are shown;
[0037] Figure 6 The shapes of the samples from Example 5 before and after heat treatment are shown;
[0038] Figure 7 The shapes of the samples from Example 6 before and after heat treatment are shown;
[0039] Figure 8 The shapes of the sample from Comparative Example 1 before and after heat treatment are shown;
[0040] Figure 9 The shapes of the sample from Comparative Example 2 before and after heat treatment are shown;
[0041] Figure 10 This demonstrates the process of measuring strain based on length changes from samples in Examples 7 and 8; and
[0042] Figure 11 The strain measurement results are shown for the patterned sample before heat treatment and the samples of Examples 7 and 8. Detailed Implementation
[0043] The invention will be described in more detail below with reference to preferred embodiments. Descriptions of techniques widely known in the art will be omitted in this description. However, those skilled in the art will readily understand the feature configurations and effects of the invention through the following embodiments, and can implement the invention without difficulty.
[0044] The inventors have discovered that thermo-mechanical methods and cooling methods applied during the heat treatment of Fe-Ni alloy foil formed by electroforming can suppress deformations such as curling caused during heat treatment, reduce the coefficient of thermal expansion, and improve mechanical properties, thereby completing the present invention.
[0045] Figure 1 This is a schematic diagram illustrating the thermomechanical heat treatment method according to the present invention.
[0046] like Figure 1 As shown, the roughly rectangular continuous heating furnace has an inlet on one side for supplying Fe-Ni alloy foil for electroforming and an outlet on the other side for discharging Fe-Ni alloy foil that has been heat-treated for a certain period of time.
[0047] The Fe-Ni alloy foil supplied to the heating furnace can be pressurized during heat treatment by using a pressurizing device or by placing a weight on it for a certain period of time.
[0048] It is preferable to apply pressure while the Fe-Ni alloy foil supplied to the heating furnace remains stationary; however, pressure can be applied even while the foil is moving, for example, when a heavy object is placed on it.
[0049] Alternatively, a tensile force can be applied to both sides of the Fe-Ni alloy foil in the travel direction along with pressure using rollers. Furthermore, a tensile force can be applied to both sides of the Fe-Ni alloy foil in the width direction perpendicular to the travel direction. That is, the pressing process using a press can be performed under the condition that a predetermined tensile force is applied along both the length and width directions of the Fe-Ni alloy foil.
[0050] Preferably, the pressure applied by the press or weight can be above 0.1 kPa, because at low applied pressures below 0.1 kPa, it is difficult to suppress deformations, such as curling or wrinkling, that occur during heat treatment.
[0051] In addition, when preparing Fe-Ni alloy foil using continuous processes such as roll-to-roll processes, the continuous process is almost unsuitable when the applied pressure is too high, or the Fe-Ni alloy foil may be damaged during the roll-to-roll process.
[0052] Therefore, the applied pressure can be less than 10 MPa, less than 5 MPa, less than 1 MPa, less than 100 kPa, less than 50 kPa, less than 10 kPa, or less than 5 kPa, more preferably less than 4.5 kPa, and most preferably less than 4 kPa.
[0053] The press duration can range from 1 second to 1 hour. When the press duration is less than 1 second, curling is barely suppressed, while when the press duration is greater than 1 hour, productivity may be excessively reduced. The ideal press duration is in the range of 10 seconds to 30 minutes.
[0054] Additionally, preferably, the Fe-Ni alloy foil can have a tensile force of less than 500 MPa, because when the tensile force is greater than 500 MPa, the Fe-Ni alloy foil may be damaged, for example, torn, during the stretching process.
[0055] Based on the electroforming conditions, the heating furnace can be maintained at a temperature ranging from 180 to 600°C. When the heating furnace is maintained at less than 180°C or greater than 600°C, it is almost impossible to maintain the coefficient of thermal expansion of the heat-treated Fe-Ni alloy foil below 3ppm / °C (preferably below 2ppm / °C, more preferably below 1ppm / °C).
[0056] In addition, in order to reduce curling and wrinkling caused during the heating process, the heating temperature can be maintained in the range of 440 to 520°C, and more preferably in the range of 450 to 510°C.
[0057] Fe-Ni alloy foil can be held in the furnace for a duration longer than the minimum time required for phase transformation, but not exceeding 12 hours. Heating durations shorter than the minimum time required for phase transformation offer almost no reduction in the coefficient of thermal expansion, which is undesirable, while heating durations exceeding 12 hours reduce the efficiency of continuous processes and result in excessive energy costs, which is also undesirable. For example, the heating duration (residence time in the furnace) can range from 10 minutes to 12 hours.
[0058] Preferably, the Fe-Ni alloy foil discharged from the heating furnace can be rapidly cooled by gas quenching. Gas quenching is a method in which the heated Fe-Ni alloy foil is placed in a sealed, predetermined chamber and cooled, vacuumed to remove air, and then injected with gas. The gas used in gas quenching is preferably an inert gas, such as argon, nitrogen, or a mixture thereof, but is not necessarily limited to these.
[0059] During gas quenching, the temperature of the gas can be below 50°C, below 40°C, below 30°C, or below 25°C.
[0060] <Example 1>
[0061] Fe-36Ni alloy foil with a thickness of approximately 10 μm, prepared by electroforming, was cut into sheets 50 mm wide and 60 mm long.
[0062] The cut sample was heated at a heating rate of 10 °C / min and at 430 °C for 30 minutes. Heating was carried out in an air atmosphere, but could also be carried out in an inert gas atmosphere such as nitrogen or argon if required.
[0063] Additionally, during heating, a 2.5 kg block (weight) was placed on the Fe-36Ni alloy foil, and a pressure of 8.17 kPa was applied for 30 minutes.
[0064] After heat treatment, gas quenching is performed, in which the heated Fe-36Ni alloy foil is placed in a sealed chamber filled with argon gas (approximately 25°C) and cooled.
[0065] <Example 2>
[0066] The same alloy foil as in Example 1 was used, and the heat treatment was performed in the same manner, except that cooling was carried out in a furnace after pressure heat treatment.
[0067] <Example 3>
[0068] The Fe-33Ni alloy foil with a thickness of about 10 μm, prepared by electroforming, was cut into sheets about 100 mm wide and about 120 mm long.
[0069] The cut sample was heated at a heating rate of 10 °C / min and then at 480 °C for 30 minutes. Heating was carried out under a vacuum atmosphere (1 × 10⁻⁶). -3 The process can be carried out in an air atmosphere or an inert gas atmosphere (such as nitrogen, argon or a mixture thereof), but in some cases, it can also be carried out in an air atmosphere or an inert gas atmosphere (such as nitrogen, argon or a mixture thereof).
[0070] In addition, during heating, a 2.5 kg block (weight) is placed on the Fe-33Ni alloy foil and a pressure of about 2.17 kPa is applied for 30 minutes. After heat treatment, gas quenching is performed, in which the heated Fe-33Ni alloy foil is placed in a sealed chamber filled with argon gas (about 25°C) for cooling.
[0071] <Example 4>
[0072] The alloy foil was heat-treated in the same manner as in Example 3, except that the heat treatment was performed at 500°C.
[0073] <Example 5>
[0074] The alloy foil was heat-treated in the same manner as in Example 3, except that Fe-36Ni alloy foil was used and the heat treatment was performed at 500°C.
[0075] <Example 6>
[0076] The alloy foil was heat-treated in the same manner as in Example 3, except that Fe-42Ni alloy foil was used and the heat treatment was performed at 500°C.
[0077] <Comparative Example 1>
[0078] The alloy foil was heat-treated in the same manner as in Example 5, except that Fe-36Ni alloy foil was used and the heat treatment was performed at 530°C.
[0079] <Comparative Example 2>
[0080] The alloy foil was heat-treated in the same manner as in Example 6, except that Fe-42Ni alloy foil was used and the heat treatment was performed at 430°C.
[0081] <Example 7>
[0082] To detect the deformation of Fe-36Ni alloy foil with a thickness of approximately 10 μm, prepared by electroforming before and after heat treatment, the foil was laser-patterned with regularly arranged octagonal holes.
[0083] Patterned Fe-36Ni alloy foil was cut into pieces 30 mm wide and 71 mm long.
[0084] The cut sample was heated at a heating rate of 10 °C / min and then heated at 450 °C for 1 hour. Heating was carried out in an air atmosphere, but could also be carried out in an inert gas atmosphere such as nitrogen or argon if required.
[0085] In addition, during the heating process, a 2.5 kg block is placed on a patterned Fe-36Ni alloy foil and pressure is applied for 30 minutes.
[0086] After heat treatment, gas quenching is performed, in which the heated Fe-36Ni alloy foil is placed in a sealed chamber filled with argon gas (approximately 25°C) and cooled.
[0087] <Example 8>
[0088] The same alloy foil as in Example 7 was used, and the heat treatment was performed in the same manner, except that cooling was performed in a furnace after heat treatment instead of gas quenching.
[0089] Evaluation of curling or wrinkling of Fe-Ni alloy foil
[0090] Figure 2 The shapes of the samples from Examples 1 and 2 are shown.
[0091] Measurements showed that the sample from Example 1, cooled by gas quenching after the same pressure heat treatment, exhibited relatively less curling than the sample from Example 2, which was cooled by furnace cooling. Therefore, it can be determined that gas quenching after pressure heat treatment may be more ideal for reducing deformation of Fe-Ni alloy foils that do not form patterns.
[0092] Figures 4 to 7 The shapes of samples from Examples 3 to 6 before and after heat treatment are shown. Figure 8 and 9 The shapes of the samples from Comparative Examples 1 and 2 before and after heat treatment are shown respectively.
[0093] like Figures 4 to 7 As shown, in the heat treatment methods of embodiments 3 to 6 according to the present invention, even in samples that initially had curls or wrinkles, almost no curls or wrinkles were observed after heat treatment.
[0094] At the same time, such as Figure 8 and 9 As shown, Comparative Examples 1 and 2 were observed to have curling and wrinkling after heat treatment, which appears to be attributed to heat treatment temperatures of 430°C and 530°C, respectively, applied to the electroformed Fe-Ni alloy foil.
[0095] Determination of the coefficient of thermal expansion of Fe-Ni alloy foil
[0096] Figure 3 The results of the measurement of the coefficient of thermal expansion of the samples from Examples 1 and 2 in the range of 50 to 100°C are shown.
[0097] like Figure 3 As shown, the sample from Example 1, which was cooled by gas quenching after the same pressure heat treatment, exhibited a relatively lower coefficient of thermal expansion in the range of 50 to 100°C than the sample from Example 2, which was cooled by furnace cooling.
[0098] Therefore, it can be seen that gas quenching is the preferred method for obtaining Fe-Ni alloy foils with a lower coefficient of thermal expansion, even with the same alloy composition, compared to other cooling methods.
[0099] Evaluation of pattern shape deformation
[0100] Figure 10 The process of measuring strain based on length changes from samples from Examples 7 and 8 is shown. Figure 11 The results show the strain measurements of patterned Fe-Ni alloy foil samples before heat treatment and samples from Examples 7 and 8.
[0101] Figure 10 A 16×16 pattern is shown on the left, where each unit consists of 16 holes in the horizontal and vertical directions based on a single octagonal hole with a symmetrical structure, and the horizontal length (hereinafter, A1), vertical length (hereinafter, A2), and diagonal length (hereinafter, B1 and B2) of the pattern are shown on the right, which were measured to compare and analyze untreated and heat-treated samples (Examples 7 and 8).
[0102] Subsequently, strain was measured based on the length change and shown. Figure 11 middle.
[0103] The heat-treated samples of Examples 7 and 8 exhibited relatively low strain levels of 0.86 to 0.40 along the four lengths A1 to B2. However, the gas-quenched sample from Example 7 showed relatively lower strain overall than the sample from Example 8, but with greater strain variation within the sample. This suggests that differences in shape deformation characteristics can exist depending on the cooling method.
[0104] According to the present invention, deformation, such as curling or wrinkling, caused during heat treatment of Fe-Ni alloy foil prepared by electroforming can be reduced.
[0105] Furthermore, according to the present invention, ultrathin Fe-Ni alloy foils with a thickness of less than 10 μm can be mass-produced.
[0106] The present invention has been described above with reference to preferred embodiments; however, it should be understood that the invention is not limited to or not construed as such. That is, various modifications and alterations can be made to the invention within the scope of the claims described below, and such modifications and alterations fall within the scope of the invention. Therefore, the invention is defined only by the scope of the claims and their equivalents.
Claims
1. A method for heat treating an Fe-Ni alloy foil, the method comprising annealing an electroformed Fe-Ni alloy foil under pressure.
2. The method according to claim 1, in, The annealing is performed at a temperature of 180° C. to 600° C. for a duration of 10 minutes to 12 hours.
3. The method according to claim 1, in, The pressure is at least 0.1 kPa.
4. The method according to claim 1, in, The Fe-Ni alloy foil is subjected to compressive and tensile forces.
5. The method according to claim 4, in, The stretching force is applied in two directions perpendicular to each other.
6. The method according to any one of claims 1 to 5, in, After the annealing, gas quenching is performed in an inert gas atmosphere.
7. The method according to claim 1, in, The annealing is performed by a continuous heat treatment process in which the Fe—Ni alloy foil is continuously fed through a heating furnace.
8. The method according to claim 7, in, During the continuous heat treatment process, the pressure is applied while temporarily stopping the travel of the Fe—Ni alloy foil.
9. The method according to claim 7, in, During the continuous heat treatment process, a tensile force is applied in the direction in which the Fe—Ni alloy foil travels.
10. An Fe-Ni alloy foil prepared by electroforming, in, The Fe-Ni alloy contains 33 mass % to 43 mass % of Ni, and The Fe-Ni alloy foil has a face-centered cubic (FCC) structure for more than 90% of the total volume, and has a (111) peak with the highest intensity determined by XRD analysis.
11. The Fe-Ni alloy foil according to claim 10, in, The Fe-Ni alloy foil has an average grain size of 50 nm or less.
12. The Fe-Ni alloy foil according to claim 10, in, The Fe—Ni alloy foil has a thickness of 15 μm or less.
13. The Fe-Ni alloy foil according to claim 10, in, The Fe-Ni alloy foil is used for a fine metal mask or an OLED packaging material.